INVENTARISASI JAMUR TINGKAT TINGGI DI KAWASAN CAGAR ALAM LEMBAH ANAI KABUPATEN TANAH DATAR SUMATERA BARAT - Jusana, Suci Pebra; Fifendy, Mades; Periadnadi, Periadnadi (Pendidikan Biologi, 2013)
AbstrakÂ Mushroom is organism of eukariot generally have many various and size. Mushroom have external form in the form of big sized fruit body so that can perceive by eyes directly. Mushroom of is include organism of heterotrof, that is organism which is life base on other organism or base on available organic materials around him. Mushroom do not have chlorophyll, berkembangbiak sexually and or by aseksual. Lembah Anaisâarea have elms, tree anakan which still nature and semaian anakan very meeting and also damp of air so that represent appropriate habitat for the growth of mushroom, so reseacher do the research about "An inventory High Level Mushroom in Cagar Alam Lembah Anai Kabupaten Tanah Datar West Sumatera". The purpose of the research is to know high level species of mushroom which found in Cagar Alam Lembah Anai Kabupaten Tanah Datar Sumatera Barat. This Research have done on June - September 2013. Method which used in this research is direct collection and observation to mushroom which in finding. From the research which have found 29 species macro mushroom. From result of research can be concluded that found mushroom in Lembah Anai Kabupaten Tanah Datar West Sumatra divided into 2 class that is Basidiomycetes and Ascomycetes, 4 ordo, 11 family and 20 gender.Â Â